Hepatitis B and C co-infection in HIV/AIDS population in the state of Michigan. (December 2013) - BUTT, Z. A.; WILKINS, M. J.; HAMILTON, E.; TODEM, D.; GARDINER, J. C.; SAEED, M.
SUMMARY A retrospective cohort study was conducted from 1 January 2006 to 31 December 2009 in Michigan to estimate the prevalence of HIV and hepatitis co-infection and identify associated factors. The prevalence of co-infection was 4·1% [95% confidence interval (CI) 3·8–4·5]. Multivariable logistic regression analysis revealed a significant association between co-infection and being male and: of Black race [odds ratio (OR) 2·0, 95% CI 1·2–3·6] and of Other race (OR 3·5, 95% CI 1·7–7·0) compared to Hispanic race. A significant association was found between co-infection and risk categories of blood products (OR 11·1, 95% CI 6·2–20·2), injecting drug user (IDU) (OR 3·6, 95% CI 2·7–4·8) and men who have sex with men/IDU (OR 3·4, 95% CI 2·4–4·9) in addition to two interactions; one between sex and current HIV status and the other between current HIV status and age at HIV diagnosis. Our results document the changing epidemiology of HIV–hepatitis co-infection which can guide preventive measures and interventions to reduce the prevalence of hepatitis co-infection.